Meningkatkan Aktivitas dan Hasil Belajar Siswa Muatan IPAS Materi Sistem Pernapasan Kelas V dengan Model Project Team dan Alat Peraga - Lusiana .; Sakerani . (CV. ITTC INDONESIA, 2024)
The aim of PTK is to describe teacher activities and analyze the increase in student activity and learning outcomes using the project team model (Project Based Learning, Teams Games Tournament and Mind Mapping) and teaching aids in the science content material on the respiratory system in humans. The subject of this research was class V at SDN Mawar 7 Banjarmasin with a total of 23 students. The research was carried out in 4 meetings. The results of this research show that teacher activity reached 100% with the criteria